2019
DOI: 10.1177/2192568219885898
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Volitional Spine Stabilization on Trunk Control During Asymmetric Lifting Task in Patients With Recurrent Low Back Pain

Abstract: Study Design: Prospective, concurrent-cohort study. Objectives: To determine the effects of volitional preemptive abdominal contraction (VPAC) on trunk control during an asymmetric lift in patients with recurrent low back pain (rLBP) and compare with matched controls. Methods: Thirty-two rLBP patients and 37 healthy controls performed asymmetric lifting with and without VPAC. Trunk, pelvis, and hip biomechanical along with neuromuscular activity parameters were obtained using 3-dimensional motion capture and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Core trunk and low back muscle atrophy has been shown to be associated with LBP and, with less strong evidence, with degenerative disc disease and spinal stenosis [6][7][8][9]. As the posterior muscles of the lumbar spine provide stability to the lumbar vertebral segments and control movement of the lumbar spine, muscular integrity plays an important role in the maintenance of global spinal alignment [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Core trunk and low back muscle atrophy has been shown to be associated with LBP and, with less strong evidence, with degenerative disc disease and spinal stenosis [6][7][8][9]. As the posterior muscles of the lumbar spine provide stability to the lumbar vertebral segments and control movement of the lumbar spine, muscular integrity plays an important role in the maintenance of global spinal alignment [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The LBP group had a higher pain score on commencement (first 10 min mark) of the prolonged stand and steadily increased over the entirety of the stand, while the group without LBP displayed a relatively stable pain score ( p < 0.001) Crosbie et al, 2013 [ 56 ] Australia To compare temporal and spatial coordination of rotations in the transverse and frontal planes of the low thoracic and lumbar spinal regions during walking at preferred and fast speeds in participants with and without a history of recurrent LBP LBP n = 19, without LBP n = 19 Age LBP: 34.0 ± 13.3 years, without LBP: 28.6 ± 5.4 years Sex: LBP 12 female, 7 male, without LBP 13 female, 6 male Pain: 2.8 ± 2.2, measured by the Visual analog scale (0–10) Disability: 4.2 (0–19 [range]), measured by the Roland Morris disability questionnaire (0–24) Trunk segmental movements recorded using a multisensor, 6-df electromagnetic tracking device ROM of trunk, pelvis, and hip joints assessed using a digital anatomical landmark For ROM, the only between-group difference was a smaller pelvic side flexion at preferred speed in patients with LBP (without LBP 8.9 ± 2.9º, LBP 7.3 ± 2º, p < 0.05) Walking speed in patients with LBP was smaller than in participants without LBP ( p = 0.02) Considering the movement coordination between segments, the phase lag at intersegmental lower thoracic and lumbar for axial rotation was significantly less in patients with LBP (21% ± 14.7) than in participants without LBP (2.8% ± 9.8) at a preferred speed ( p < 0.05). Phase lag at intersegmental side flexion and axial rotation was significantly less in patients with LBP (- 9% ± 9.3) than in participants without LBP (0% ± 11.2) at a preferred speed ( p < 0.05) The movements of the pelvis during axial rotation were significantly greater in patients with LBP (preferred speed 0.99 ± 0.01 m/s, fast speed 0.98 ± 0.01 m/s) than in participants without LBP (preferred speed 0.98 ± 0.05 m/s, fast speed 0.96 ± 0.05 m/s, p < 0.05) Haddas et al, 2019 [ 57 ] United States To determine the effects of volitional preemptive abdominal contraction and recurrent LBP on trunk mechanics and neuromuscular control during an asymmetrical 1-m box-lift task LBP n = 32, without LBP n = 37 Age LBP: 21.6 ± 2.2 years, without LBP: 20.4 ± 4.2 years Pain: in the same day 2.0 ± 0.9, in the last week 3.9 ± 1.5, worst pain in the last week 4.8 ± 1.9, measured by the Visual analog scale (1–10) EMG of external oblique and gluteus maximus muscle, 3D spine and pelvic joint kinematics using a Vicon motion during asymmetric lifting The LBP group demonstrated reduced EMG activity for the external oblique muscle (80.6 ± 5.5% maximum voluntary contraction) at the initial position of the lifting compared to participants without LBP (92.9 ± 5.6% maximum voluntary contraction, p = 0.01). Furthermore, the LBP group performed the lift with smaller glute...…”
Section: Resultsmentioning
confidence: 97%
“…Of the 54 studies included, nine assessed range of motion [ 22 26 , 28 30 , 72 ], 16 assessed kinematics [ 35 43 , 45 50 , 68 ], four strength [ 31 34 ], seven electromyography [ 17 , 18 , 27 , 51 54 ], and 18 assessed more than one outcome (six assessed kinematics and range of motion [ 44 , 56 , 59 , 60 , 63 , 69 ], three range of motion and electromyography [ 58 , 65 , 66 ], two strength and range of motion [ 67 , 71 ], one strength, range of motion, and electromyography [ 16 ], one electromyography and kinematics [ 55 ], two electromyography and kinematics [ 57 , 61 ], one electromyography, kinematics, and strength [ 62 ] and two kinematics and strength[ 64 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has identified repetitive trunk flexion-extension (FE) movement as one of the key factors (Marras, 2000;Weiner et al, 2006). This activity, which is dependent on multiple control parameters, including speed, physical load, and symmetry/asymmetry, increases the susceptibility of workers to injuries, particularly LBP, and instigates numerous management challenges within work settings (Frymoyer et al, 1980;Haddas et al, 2019;Hendershot et al, 2011). Research also suggests that the control parameters associated with this activity impact the underlying active, passive, and neuromuscular control subsystems whose contribution regulates the dynamic stability of the trunk (Hoffman & Gabel, 2013).…”
Section: Introductionmentioning
confidence: 99%